Do Former Elite Athletes Live Longer? New Evidence From German Olympic Athletes and a First Model Description - Thieme, Lutz; Fröhlich, Michael (Frontiers in Sports and Active Living, 2020)
The positive effects of physical activity and recreational sports on health have been well-examined and are well-proven. In contrast, the consequences of extensive elite sports on life expectancy and mortality rates have been described in significantly less unique and comprehensive terms. There is a lack of models that systematically summarize the factors influencing the life span of elite athletes. Therefore, this study identifies the difference between all 6,066 German participants in Olympic Games between 1956 and 2016 and the total population, as well as between participants from the Federal Republic of Germany (FRG) and the German Democratic Republic (GDR), and between the genders. Currently, the survival rate of German Olympians is lower compared to the general population. On the contrary, it was found that Olympic success represents a linear risk for survival probability. While different types of sports do not exhibit any differences, gender and origin (FRG vs. GDR) do represent a significant risk factor. These results are combined with the current state of research to create an impact model of factors influencing the life span of elite athletes.